Oral Mucositis in Pediatric Oncology Patients: A Nested Case-Control to a Prospective Cohort - Ribeiro,Isabella Lima Arrais (2020)
Abstract This study aimed to evaluate the factors associated with the occurrence of severe oral mucositis (SOM) in pediatric oncology patients during the chemotherapeutic treatment. This is a nested case-control to a prospective cohort that monitored 105 patients for 10 consecutive weeks after the beginning of the chemotherapy treatment. Logistic regression was used to identify the factors associated with SOM, by group of malignancy (hematologic or solid tumors) (Sig.=5%). To patients with hematologic tumors were found factors associated with SOM in two weeks of treatment: in the 6th week (increase in frequency of chemotherapy doses (OR=3.02)) and in the 7th week (female sex (OR=21.28); and increase in frequency of chemotherapy doses (OR=2.51)); and to patients with solid tumors were found factors associated with SOM in five weeks of treatment: in the 1st week (female sex (OR=14.43); age increase (OR=1.24)); in the 2nd week (Miscellany (OR=6.39)); in the 5th week (Antimetabolites (OR=17.44); Miscellany (OR=45.42); and platelets reduction (OR=1.12)); in the 6th week (creatinine increase (OR=1.63)); and in the 7th week (creatinine increase (OR=2.39)). For patients with hematologic tumors, to be female, and the increase in the frequency of chemotherapy doses increased the risk for SOM and for patients with solid tumors, to be female, the increase in age and in level blood concentration of creatinine, the reduction in number of platelets and the use of chemotherapy with miscellany and antimetabolites agents were associated with an increase in risk for occurrence of SOM.